Business Ethics and Employees Satisfaction in Selected Micro and Small Enterprises in Ilorin Metropolis, Kwara State, Nigeria - Bello, Fatai; Isiaka, Sulu Babaita; Kadiri, Ismaila Bolarinwa (NIU Journal of Social Sciences; Vol 4 No 3 (2018): KIU Journal of Social Sciences, Vol. 4 No. 3, September 2018, 2018)
Micro and small Enterprises (MSE) in Nigeria continue to fail despite huge yearly sectorial allocations, policies and intervention funds that are geared towards making them the driving force of the economy. This study examined ethical practices among MSEsâ€™ owner/managers as well as how they apply same in their managerial activities. It also examined the relationship between ethics and the employee satisfaction.  The study used cluster sampling to select eighty-nine (89) business owners and one hundred and seventy-eight (178) employees of the selected businesses. The business cut across ten distinct MSEs sub-categories operating within Ilorin metropolis, Kwara State, Nigeria.. Data were collected through self-administered questionnaires and analyzed using descriptive, comparative, correlation and student t-test of significance. The result obtained further showed that the owner/managers do not apply ethical practices and behaviour in their managerial style despite having substantial understanding of what constitute ethics and ethical practices. The results obtained shows that the employees perceive that their owner-managers lack ethical leadership with the mean of 2.753 falling below the 3.0 cut-off point. This was shown to have negative impact on the job satisfaction of their employees and probably responsible for the continued under-performance and failure of MSEs in Nigeria. Based on these findings, it was recommended that MSEâ€™s owner managers should introduce ethical values to their employee through role modeling and consistent practice of the same. Effort should be made to reward those who espoused high moral culture and deter those who flout the moral code.